Transcriptome analysis of the effect of pyrroloquinoline quinone disodium (PQQ·Na(2)) on reproductive performance in sows during gestation and lactation - Zhang, Boru (J Anim Sci Biotechnol, 2019)
BACKGROUND: Pyrroloquinoline quinone (PQQ), which is a water soluble, thermo-stable triglyceride-quinone, is widely distributed in nature and characterized as a mammalian vitamin-like redox cofactor. The objective of this study was to investigate the effects of pyrroloquinoline quinone disodium (PQQ·Na(2)) on reproductive performance in sows. RESULTS: Dietary supplementation with PQQ·Na(2) significantly increased the total number of piglets born, the number of piglets born alive and the born alive litter weight. It also increased the antioxidant status in the placenta, plasma and milk. The concentration of NO was significantly increased in the plasma and placenta. RNA-seq analysis showed that 462 unigenes were differentially expressed between the control (Con) treatment and PQQ treatment groups. Among these unigenes, 199 were upregulated, while 263 unigenes were downregulated. The assigned functions of the unigenes covered a broad range of GO categories. Reproduction (27, 7.03%) and the reproduction process (27, 7.03%) were assigned to the biological process category. By matching DEGs to the KEGG database, we identified 29 pathways. CONCLUSIONS: In conclusion, dietary supplementation with PQQ·Na(2) in gestating and lactating sows had positive effects on their reproductive performance. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s40104-019-0369-y) contains supplementary material, which is available to authorized users.